Vowel qualities in monosyllabic words in Namibian English - Saloranta, Antti; Haapanen, Katja; Peltola, Kimmo U.; Tamminen, Henna; Uwu-khaeb, Lannie; Peltola, Maija S. (Journal of Monolingual and Bilingual Speech, 2024)
This study investigated how Namibian English speakers produce vowel qualities in controlled speech. Participants were 14 proficient Namibian English speakers, who produced monosyllabic English CVC words, presented in orthographic form. The first and second formant values were extracted from the speakers’ productions to determine the vowel qualities in each word. The formant values produced by the Namibian English speakers were then compared to those produced by nine British English speakers, obtained from a previous study, in order to examine how Namibian English vowel qualities relate to British English vowel categories. The results showed a great deal of variation and overlap in the Namibian vowel categories, particularly in the close front vowels and open and close back vowels. This resulted in the formation of five to six clusters of vowel qualities. This is likely an effect of the varied linguistic backgrounds of the participants. Furthermore, the Namibian English vowels differed significantly from most British English vowels, especially in the F2 formant. Some commonalities with earlier research into Namibian English vowel qualities was found in the fronting, backing and mergers of some vowel categories.